Analysis of variance in augmented block design and Scott-Knott’s test in hybrid corn selection studies - Malaquias, Juaci Vitoria; Amabile, Renato Fernando; Zorzo, Felipe; Melo, João Victor Pinheiro; Fagioli, Marcelo (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to present a methodological alternative for studies of the characterization and selection of corn (Zea mays) genotypes, through the joint analysis of variance of an augmented block design, using Scott-Knott’s test, and to present the hybrids selected from the adopted strategy, to show its efficiency. For the application of the methodology, a case study was used: the selection of superior corn hybrids for the Brazilian Cerrado. In four locations, 70 experimental hybrids were evaluated in an augmented block design without replicates, with three controls replicated once in each block. The analysis of experimental groups applied to the augmented block design, followed by genotype classifications by Scott-Knott’s multiple comparison test, is a viable alternative for studies with a low number of replicates and a large number of genotypes. Based on the tested methodology, the following experimental hybrids are selected for grain yield: HT007, HT008, HT018, HT004, HT024, HT005, and HT071.